Resources-Based View (RBV) as A Strategy of Company Competitive Advantage: A Literature Review - Sugiarno, Yuventius; Novita, Dina (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Recourse Based-View (RBV) as a theory of strategic management is still relevant to be used as a tool to analyze the competitive advantage of a company or organization. Companies or organizations have an interest in exploring the potential of internal resources to increase competitive advantage in the midst of increasingly fierce competition. This study aims to conduct a literature review on the development of RBV as a strategic theory that prioritizes the company's internal resources in dealing with external forces as proposed by industrial organization theory. Descriptive qualitative approach was used as a method of data collection and discussion. Journal articles and books on RBV and competitive advantage are collected as basic data and then analyzed by determining keywords such as: RBV, competitive advantage, dynamic capabilities, company external strengths, tangible resources, intangible resources, knowledge or intellectual capital, market competition. The results show that the development of RBV as a company's competitive advantage strategy can be implemented while developing the ability to understand the company's or organization's external environment. Intangible resources such as knowledge become the pivot for a balance meeting between RBV and industrial organization theory.